POLEMIK PENERAPAN ATURAN PASAL 209 KOMPILASI HUKUM ISLAM TENTANG KETENTUAN WASIAT WAJIBAH (Ahkam: Jurnal Hukum Islam, 2024)
The existence of the articles on wills and testaments in the Compilation of Islamic Law has given rise to many legal disputes and disparities by judges. On the one hand, he confirms that he is an adopted child, on the other hand he denies it. As much, there is a need for clear rules regarding with adopted child recognized as a heir. The provisions on obligatory williay in the KHI are contrary to the text of the Al-Qur'an because adopted children are not included as heirs. The methodology in this research was library research using a descriptive qualitative approach. The focus of the research is to answer how the polemic occurred when and after the formulation of article 209 regarding the will of wajibah and what the ijtihad method was used as the basis in producing the provisions of the will of wajibah. The results of the research revealed the fact that there is no different opinion during the formulation of the KHI, no different opinion emerged after the formulation of the KHI by two groups of thought from Islamic law academics or Indonesian Islamic organizations regarding the provisions of mandatory wills, regarding the following thouhgts: First, the text-based group, namely the group that opposed the provisions of the will of wajibah because it violates the nas qat'i. Hence, it is necessary to revise and improve the dictum of article 208, including the application of the article wasiat wajibah with the condition that it is approved by the heirs, the heir leaves a large amount of assets and the adopted child's share cannot exceed the smallest share among the true heirs; Secondly, the group has an assimilative pattern, fully accepting the will of wajibah with a new interpretive approach by proposing revisions. The Ijtihad method in article 209 is a form of combining intiqo'i (selective) ijtihad with insha'i (creative) ijtihad.
Keywords: polemic; pasal 209; Kompilasi Hukum Islam; wasiat wajibah